Peningkatan Literasi Keuangan Pada Pelaku Usaha Tempe Melalui Pelatihan Pembukuan Keuangan di Kelurahan Tembalang Semarang: - - Fariha Azzahra; Dina Kharisma; Elisa Teguh Prasetyani; Nasyya Kumalarahmadani; C. Tri Widiastuti - (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The purpose of community service activities is to provide simple bookkeeping training and mentoring for Tempe home-based businesses. In running a business, the business actors have not made financial records/books in accordance with applicable regulations. The problem faced by business actors is the lack of financial literacy/knowledge. By providing knowledge, training, and assistance, business actors can increase their knowledge so that they can find their expenses, incomes, profits, and developments. The method used is a site survey, socialization, training, and assistance in making financial books. The result of this training activity is increased knowledge in making bookkeeping by 89.09%, business actors can do financial bookkeeping, separate personal and business finances, know the benefits obtained and make good decisions.